2011
DOI: 10.1016/s0929-6646(11)60057-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study of Hospitalization Associated With Respiratory Syncytial Virus Infection in Taiwanese Children Between 2004 and 2007

Abstract: RSV infection occurs biennially with peaks in spring and fall in Taiwan. Patients with underlying diseases need longer hospital and ICU stays and incur higher medical costs. Younger age, prematurity, congenital heart disease and cerebral palsy are predictors of ICU care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 31 publications
1
36
1
2
Order By: Relevance
“…RSV infection has biennial pattern with peaks in spring and fall in northern Taiwan [22] but no significant seasonality in southern Taiwan [23]. Furthermore, based on the database of National Health Insurance in Taiwan, RSV related hospitalization occurs throughout the whole year with peaks in spring and fall, especially in prematurity and in patients with CHD [5]. In Taiwan, there is no exact “RSV season”.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RSV infection has biennial pattern with peaks in spring and fall in northern Taiwan [22] but no significant seasonality in southern Taiwan [23]. Furthermore, based on the database of National Health Insurance in Taiwan, RSV related hospitalization occurs throughout the whole year with peaks in spring and fall, especially in prematurity and in patients with CHD [5]. In Taiwan, there is no exact “RSV season”.…”
Section: Discussionmentioning
confidence: 99%
“…In countries with temperate climates that have well defined RSV seasons, approximately 50% of RSV-related hospitalization occurs in infants younger than 6 months [3], [4]. In Taiwan, the population-based annual incidence of RSV-associated hospitalization was highest under 6 months of age and 70% of the patients with RSV-associated hospitalization are infants [5]. Predisposing conditions for the development of serious RSV disease include young age, prematurity, chronic lung disease (CLD), congenital heart disease (CHD), neuromuscular impairment, immunodeficiency, and Down syndrome [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…For children with bronchiolitis, García et al [57][58][59] found three predictors of ICU admission: virus species (RSV vs. non-RSV), atelectasis/condensation, and co-infection. For children with RSV infection, Verger et al [60][61][62][63][64][65][66][67][68] identified several risk factors for ICU admission: immature lung development, prematurity, chronic lung disease, congenital heart disease (defined as congestive heart failure, cyanosis, or pulmonary hypertension), neuromuscular impairment, high nasal RSV viral load, surfactant protein A2 polymorphism, age < 6 weeks, neurological disease, cerebral palsy, male gender, lung consolidation, lethargy, grunting, high arterial PaCO 2 , an ED visit in the past week, presence of moderate to severe retractions, inadequate oral intake upon presentation in the ED, and mental retardation.…”
Section: Predicting Icu Admissionmentioning
confidence: 99%
“…El VSR presenta un patrón predictivo de enfermedad dentro de la comunidad han registrado epidemias en muchos países, incluyendo Australia [12], Reino Unido donde el pico de la epidemia corresponde a los meses fríos del año. En los Estados Unidos y Taiwán existe una variación estacional mayor en la cual el pico varía desde el otoño, invierno y principios de la primavera, el cual dura entre cuatro o cinco meses [4,15,16].…”
Section: Características Del Virusunclassified
“…Es muy bien conocido que el virus sincicial respiratorio (VSR) es la causa principal de la infecciones respiratorias más serias que ocurren en la infancia [4,5] …”
Section: Introductionunclassified